2004
DOI: 10.1007/s00535-004-1381-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Helicobacter pylori in Japanese children with gastritis or peptic ulcer disease

Abstract: H. pylori is the most important causal factor for the development of duodenal ulcer in childhood. While H. pylori infection appears to be a risk factor in gastric ulcer, other causes are responsible for most cases. Nodular gastritis is the most common type of H. pylori gastritis in childhood. Chronic infection with H. pylori is associated with anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
3
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 27 publications
(23 reference statements)
6
93
3
2
Order By: Relevance
“…However, H. pylori incidence in children with chronic gastritis was higher than that (25.6 %) reported in a recent study (Wong et al, 2005). The results of the present study were similar to those of a Japanese study (Kato et al, 2004).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, H. pylori incidence in children with chronic gastritis was higher than that (25.6 %) reported in a recent study (Wong et al, 2005). The results of the present study were similar to those of a Japanese study (Kato et al, 2004).…”
Section: Resultssupporting
confidence: 91%
“…The incidence of the infection in children ranges from 10 to 80 %, and is high in developing and some other countries (Torres, 2000; Janulaityte-Gunther et al, 2005;Kato et al, 2004). H. pylori infection is most often intrafamilial and spreads by oral-oral or faecal-oral transmission (Megraud, 2003;Mladenova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the changing food habits and westernization in our country or due to increased diagnosis by endoscopy.A retrospective Japanese study published in 2004 concluded that H. pylori was significantly linked to duodenal ulcer and gastric ulcers in the age group of 10-16 years, but not in the age group of 9 years and under. 9 A 14 year boy with severe malnutrition who presented with acute abdomen, loose stools and right iliac fossa tenderness was diagnosed as Crohn's disease based on CT enterography and colonoscopy. He had been treated as abdominal tuberculosis in the past with multiple courses of anti-tuberculosis drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pooled analysis of early reports (from 1983 to 1994) has demonstrated that the prevalence of H. pylori in children with duodenal ulcer was relatively higher (ranging from 33% to 100%, with a median value of 92%), compared with children with gastric ulcer (ranging from 11% to 75%, with a median value of 25%) [104]. A more recent retrospective study (from 1995 to 2001) from Japan confirmed a very high prevalence of H. pylori in antral gastritis and duodenal ulcer (98.5% and 83%, respectively), also identifying H. pylori as a risk factor for the development of gastric ulcer although with a lower prevalence of infection (less than 50%) [101]. Finally, in a Chinese study, it was reported that among 43 Chinese children suffering with peptic ulcer disease, 37 had duodenal ulcer, of which 21 were H. pylori positive, while only six had gastric ulcer, of which only two were positive for the infection [7].…”
Section: Nevertheless Specific Populations Such As Immigrants and Rumentioning
confidence: 98%
“…In a recent large European multicenter study, including 1233 symptomatic children with H. pylori infection, peptic ulcer disease was diagnosed in less than 5% of children younger than 12 years of age and in ≈10% of teenagers [8]. Interestingly, other studies indicate a higher association of H. pylori with peptic ulcer in adolescents than in younger children [100,101]. But, the prevalence of H. pylori-positive ulcers in children also differs between countries and this is not completely explained by the prevalence of the infection in the population studied.…”
Section: Prevalence Of H Pylori-associated Gastric and Duodenal Ulcementioning
confidence: 99%